Effect of initial powder type on the hydrogen storage properties of high-pressure torsion consolidated Mg. (31st August 2017) - Panda, Subrata; Fundenberger, Jean-Jacques; Zhao, Yajun; Zou, Jianxin; Toth, Laszlo S.; Grosdidier, Thierry
Abstract: While severe plastic deformation (SPD) on bulk samples has been widely applied for modifying the H-sorption properties, there has been little attention towards the use of SPD on powder materials. In this context, the aim of the present work was to compare the H-storage properties of high-pressure torsion (HPT) consolidated products obtained from two distinct Mg powder precursors: atomized micro-sized and condensed ultrafine powder particles. The results showed that the nature of the initial powder precursor had a pronounced effect on the H-sorption behavior. The HPT product obtained from the condensed ultrafine powder showed faster absorption kinetics than the consolidated product obtained from the atomized powder. However, the HPT product obtained from atomized powder could absorb more hydrogen and showed faster desorption kinetics corresponding to a lower activation energy. These results are discussed by taking into account the effectiveness of the HPT process to refine the grain sizes and differences in the dispersion of fine MgO oxide particles. Highlights: Atomized micro-sized and condensed ultrafine Mg powders were processed by HPT. From atomized powder, the micro-HPT product contained 1 μm equiaxed grains. From condensed powder, a nano-HPT MgO + elongated Mg composite was obtained. The nano-HPT product showed faster absorption kinetics than the micro-HPT one. The micro-HPT had higher storage capacity and faster desorption kinetics.